Pengembangan Media Pembelajaran Tematik Berbasis Android Menggunakan Smart Apps Creator (SAC) pada Sekolah Dasar - Hamidah, Allinda; Nisa', Choirun (Fakultas Agama Islam Universitas Billfath, 2022)
This research and development aim to produce products in the form of interactive learning media based on Android with the help of Smart Apps Creator (SAC) software, for valid, practical, and effective Thematic learning for students. The media contains teaching materials about Capital Letters and Punctuation, equipped with audio, illustrated examples, and practice questions. This type of research is Research and Development (RnD) research using the ADDIE development model. The stages/steps of the ADDIE development model, namely 1) Analysis, namely analyzing problems, user needs, and systems for teachers and students; 2) Design, namely the design of the product to be developed; 3) Development, namely product development and manufacture; 4) Implementation, namely the process of testing the validation of experts and their application; and 5) Evaluation, namely conducting an evaluation with the aim of completing the shortcomings and needs so that the product is feasible to apply. This application product was validated by 3 experts, namely material (content) experts, media, design, practicality tests carried out by the homeroom teacher, as well as opinions from students to get responses from the application of this application. Based on the research that has been done, the data obtained and processed resulted in an average score of 4.1 material experts, 4.2 media experts, and 4.4 design experts, which these three experts were included in the valid category; the average score of the practicality assessment of 4.5 is included in the practical category, and the effectiveness assessment score has increased by 0.59 including in the high category and is said to be effective, it can be concluded that android-based interactive learning media is suitable and feasible to be applied as a learning medium. And can help the learning process to be more practical and effective in thematic learning.